FINANCIAL FITNESS: A GUIDE TO BOOSTING YOUR MONEY MANAGEMENT SKILLS: FINANCIAL FITNESS: A GUIDE TO BOOSTING YOUR MONEY MANAGEMENT SKILLS - Supeno, Bambang; Jamil, Poppy Camenia; yulyanti, Sinta (PENANOMICS: International Journal of Economics, 2024)
This research investigates the relationships between financial literacy, budgeting practices, financial behavior, and money management skills among individuals at BCA KCU Bandung. Using quantitative methods and path analysis, the study examines direct and indirect effects to uncover how these variables interact. The findings highlight significant direct relationships, such as the impact of effective budgeting on financial behavior and money management skills. Indirectly, financial literacy and budgeting practices contribute to improved money management skills through fostering responsible financial behaviors. These insights underscore the importance of promoting financial education and practical budgeting strategies to empower individuals in making informed financial decisions and enhancing their financial well-being. This study contributes to the field by offering actionable insights for financial education initiatives aimed at fostering financial stability and competence among diverse populations.